2021
DOI: 10.1155/2021/6669366
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hydrodynamic Pressure Distribution in Reservoir of Concrete Gravity Dam under Vertical Vibration Using an Analytical Solution

Abstract: Fluid-structure interaction causes a hydrodynamic force, which can be exerted to the dam and affects its response. The effect of vertical excitation of ground motion on dynamic behavior of concrete gravity dam is the most important because of the interaction between foundation and reservoir. So, the foundation-reservoir interaction should be taken into account in designing concrete dams. In most studies, the effects of the vertical component of vibration have been ignored. While in vertical vibration, due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Chopra [5] revealed that using added mass to simulate hydrodynamic effects ignores the water compressibility, which would lead to unreliable decisions in the seismic analysis of concrete dams. Khiavi et al [28] investigated the hydrodynamic response of a concrete gravity dam and reservoir under vertical vibration using an analytical method. Amina et al [29] conducted a series of modal analyses of the Brezina concrete arch dam based on the Lagrangian and added mass approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Chopra [5] revealed that using added mass to simulate hydrodynamic effects ignores the water compressibility, which would lead to unreliable decisions in the seismic analysis of concrete dams. Khiavi et al [28] investigated the hydrodynamic response of a concrete gravity dam and reservoir under vertical vibration using an analytical method. Amina et al [29] conducted a series of modal analyses of the Brezina concrete arch dam based on the Lagrangian and added mass approaches.…”
Section: Introductionmentioning
confidence: 99%
“…This old method was an easy one since the technology was not well developed in the past as now. This method considers the inertia force of the dam, and the hydrodynamic forces, which developed from water waves (Nath 1971;Melo & Sharma 2004;Pasbani Khiavi et al 2021). The weight of the theoretical sliding mass 'M' and the seismic coefficient 'k' are used to measure the magnitude of the static inertial load, which represents the seismic load 'F'.…”
Section: Pseudo-static Methods (Psm)mentioning
confidence: 99%
“…Pasbani Khiavi et al (2021) examined the responses to achieve the optimal body stiffness using probabilistic and uncertainty methods after evaluating the effect of Young Modulus of both the body concrete and the foundation as strength parameters for concrete arch dams. The dam-reservoir-foundation system's finite element analysis was completed using ANSYS software, and the Monte Carlo method, a new method for parametric study and sensitivity analysis, was used for uncertainty analysis.…”
Section: Research History and Related Workmentioning
confidence: 99%
“…It is difficult to use conventional methods, which support only triangle and quadrilateral grids, to solve and compute the hydrodynamic pressure of a reservoir with polygonal grids under an earthquake. In the analysis of the seismic safety evaluation of dams, the hydrodynamic pressure is an important influencing factor that cannot be ignored [30][31][32][33]. Considering the important influence of hydrodynamic pressure on dam response, it is an urgent problem, which until now remains to be solved, for a cross-scale dynamic dam analysis system based on a polyhedron SBFEM.…”
Section: Introductionmentioning
confidence: 99%